Minimally invasive pancreatoduodenectomy. Issue 3 (March 2017) - ,; Asbun, Horacio J.; Barkun, Jeffrey; Besselink, Marc GH.; Boggi, Ugo; Conlon, Kevin CP.; Han, Ho-Seong; Hansen, Paul D.; Kendrick, Michael L.; Kooby, David A.; Montagnini, Andre L.; Palanivelu, C.; et al.
Abstract: Background: Minimally invasive pancreatoduodenectomy (MIPD) is increasingly performed with several institutional series and comparative studies reported. The aim was to conduct an assessment of the best-evidence and expert opinion on the current status and future challenges of MIPD. Methods: A systematic review of the literature was performed and best-evidence presented at a State-of-the-Art conference on Minimally Invasive Pancreatic Resection. Expert panel discussion and audience response activity was used to assess perceived value and future direction. Results: From 582 studies, 26 comparative trials of MIPD and open pancreatoduodenectomy (OPD) were assessed for perioperative outcomes. There were no randomized controlled trials and all available comparative studies were determined of low quality. Several observational and case-matched studies demonstrate longer operative times, but less estimated blood loss and shorter length of hospital stay for MIPD. Registry-based studies demonstrate increased mortality rates after MIPD in low-volume centers. Oncologic assessment demonstrates comparable outcomes of MIPD. Expert opinion supports ongoing evaluation of MIPD. Conclusion: MIPD appears to provide similar perioperative and oncologic outcomes in selected patients, when performed at experienced, high-volume centers. Its overall role in pancreatoduodenectomy needs to be better defined. Improved training opportunities, registry participation and prospective evaluation are needed.